2017
DOI: 10.1007/s12350-015-0320-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of absolute myocardial blood flow in humans using dynamic cardiac SPECT and 99mTc-tetrofosmin: Method and validation

Abstract: Background The objective of this study was to measure myocardial blood flow (MBF) in humans using 99mTc-tetrofosmin and dynamic single photon emission computed tomography (SPECT). Methods Dynamic SPECT using 99mTc-tetrofosmin and dynamic positron emission tomography (PET) was performed on a group of 16 patients. The SPECT data were reconstructed using a 4D-spatiotemporal iterative reconstruction method. The data corresponding to 9 patients were used to determine the flow-extraction curve for 99mTc-tefrofosmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…The feasibility of this approach has been demonstrated in a large animal model, 155 but at this time SPECT MBF and MFR measurements in humans are very new. While the results have been very encouraging, investigations with both conventional rotating systems 156,157 and non-rotating cardiac cameras 15,17,158,159 have been limited to single-center feasibility studies. While the benefits of PET-based MBF/MFR are clear, [160][161][162][163] no published study has currently evaluated the incremental diagnostic and prognostic value of SPECT MBF and MFR measurements; more investigations are ongoing in this area.…”
Section: Spect Myocardial Blood Flow Quantitation Introductionmentioning
confidence: 99%
“…The feasibility of this approach has been demonstrated in a large animal model, 155 but at this time SPECT MBF and MFR measurements in humans are very new. While the results have been very encouraging, investigations with both conventional rotating systems 156,157 and non-rotating cardiac cameras 15,17,158,159 have been limited to single-center feasibility studies. While the benefits of PET-based MBF/MFR are clear, [160][161][162][163] no published study has currently evaluated the incremental diagnostic and prognostic value of SPECT MBF and MFR measurements; more investigations are ongoing in this area.…”
Section: Spect Myocardial Blood Flow Quantitation Introductionmentioning
confidence: 99%
“…In this issue of Journal of Nuclear Cardiology, a study by Shershta et al 5 analyzes the feasibility results of dynamic flow measurements with 99m Tc-tetrofosmin SPECT. Several methodological aspects of this study merit highlighting.…”
Section: Is Flow Measurement Feasible On the Conventional Spect Cameras?mentioning
confidence: 99%
“…While there is not yet an accepted 'standard basis' for 4D image reconstruction, the authors have shown promising results using their chosen shape functions in several earlier simulation and human studies. [3][4][5] If these shape functions can provide a good fit to the measured dynamic data, then the modeled tracer distribution or 'parametric images' can be visualized post hoc at any time point from the start to end of the scan. This has the potential to allow visualization of tracer uptake in very short time intervals (i.e., 5 seconds in the present study) but with the image quality and count statistics derived from the much longer dynamic scan.…”
mentioning
confidence: 99%